IMPORTANCE OF PORT-SUPPLY CHAIN INTEGRATION IN ENHANCING MANUFACTURING CAPACITY UTILISATION (MCU) IN NIGERIA - ONI, BABATOPE GABRIEL; OLUWAKOYA, ADENIYI OLUFEMI; ADEYINKA, PETER AJAYI (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2024)
The utilisation of manufacturing capacity at 57% holds significant implications for Nigerian consumers. This paper explores the impact of integrating port supply chains on manufacturing capacity utilisation in Lagos and Ogun States, Nigeria. Secondary sources were employed to collect data on container port throughput (PT) and manufacturing capacity utilisation (MCU) from the Nigerian Port Authority and the Manufacturers Association of Nigeria between 2014 and 2021. The study reveals a positive relationship between Tin Can Port PT and Food and Beverages MCU, indicating that a unit change in Tin Can Island port throughput results in a 35.4% increase in manufacturing capacity utilisation. Conversely, a percentage change in Apapa port throughput only leads to a 0.08% increase in manufacturing capacity utilisation. The findings suggest that port supply chain integration can enhance MCU, provided the policy is tailored to specific ports. The study emphasises the pivotal role of effective policies in boosting Nigeria’s manufacturing capacity utilisation, particularly in the food and beverages sector.